Geochemical evaluation of crude oil in the Franquera Oil Field and nearby oil reservoirs in the southeastern region of the Maracaibo Lake basin. - Grobas, Jacqueline; Escobar, Marcos (Rev. Téc. Fac. Ing. Univ. Zulia)
Geochemical evaluation of oil from a well recently drilled in the southeast area of Maracaibo Lake (FRA-1X, Franquera oil field) and its comparison with 5 crude oils from nearby fields, led to the conclusion that these geochemically correlated marine mature oils could be the result of the mixture into the reservoir of petroleum formed by two pulses of generation of the La Luna Formation source rocks, which fed the study area in different geological periods (Eocene and Miocene-Recent).